A new substitute host and its effects on some biological properties of Ooencyrtus kuvanae. Issue 6 (22nd March 2017) - Tunca, Hilal; Venard, Marine; Colombel, Etty-Ambre; Tabone, Elisabeth
Abstract: Lymantia dispar (L.) (Lepidoptera: Lymantriidae), commonly known as the gypsy moth, is a serious forest pest, and beneficial insects are particularly important for reducing its population numbers. Ooencyrtus kuvanae (Howard) (Hymenoptera: Encyrtidae) is an arrhenotokous, solitary egg parasitoid of L. dispar . In this study, we evaluated a new substitute host, Philosamia ricini (Danovan) (Lepidoptera: Saturniidae) for O. kuvanae . We investigated some of the biological effects of O. kuvanae on P. ricini eggs. In this context, the importance of the age of the female parasitoid (1, 3 or 5 days old), host age (1–2 and 3–4 days old) and host number (40, 60 and 80 host eggs) were examined under laboratory conditions (25 ± 1 °C, 65 ± 5% relative humidity and a 16 : 8 h photoperiod [light : dark]). The highest rate of offspring production (89.90%) occurred with 40 (1–2-day-old) host eggs and 5-day-old females. The mean developmental period ranged from 16.5 ± 0.08 days to 18.7 ± 0.08 days. The mean lifespan of the parasitoid was 51.10 ± 1.1 ( n = 60) days with bio-honey and 3.92 ± 0.14 ( n = 60) days without food. The mean fecundity was 68.88 ± 3.22 offspring/female. Peak adult emergence occurred between 2 and 9 days. The mean oviposition and mean post-oviposition periods of the female parasitoid were 22.76 ± 1.37 days and 13.64 ± 1.40 days, respectively. O. kuvanae was reared for more than ten generations on the eggs of P. ricini . Based on our findings, P. ricini can be used to rear O. kuvanae for the biological control of L. dispar .